Estimating participation responses using transfer program reform - Spencer Bastani; Ylva Moberg; Håkan Selin (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2016)
In this paper we estimate labor force participation responses for married women in Sweden using population-wide register data and detailed information about individuals' budget sets. For identification we exploit a reform in the system for housing allowances in 1997 which affected participation tax rates for households with/without children differently. Using a simple theoretical framework we provide a structural interpretation of our estimates and highlight how the employment response depends on the employment level. Our central estimate of the participation elasticity is 0.13. When splitting the treated sample into four quartiles based on the wife's skill level we find that the participation elasticity is more than twice as large for the lowest-skill sample than for the highest-skill sample.
Keywords: H20; J22; 330; labor supply; social assistance; housing allowance; in-work tax credits; take up of transfer programs